Green Chemical Oxidation Using Iron Nanoparticles for Removal of Azo Dye in Simulated Wastewater: Kinetics and Thermodynamics - Ahmed K. Hassan; Mahdy S. Jaafar; Luay Q. Hashim; Ahmed M. Rezooqi; Mohammed F. Hashim (Iraqi Journal of Industrial Research)
In this research, the greener catalyst of iron nanoparticles (G-FeNPs) was synthesized from the reduction of iron (III) salt by the extract of used green tea leaves waste. The product was characterized by SEM, AFM, and FTIR, while the zeta potential was measured to study the stability of G-FeNPs. The degradation of the anionic dye Eriochrome Blue Black R (EBBR) from an aqueous solution using a Fenton-like process catalyzed by G-FeNPs has been studied. The effects of catalyst dosage, hydrogen peroxide concentration, and pH, initial concentration of EBBR dye, contact time, and temperature were studied and evaluated for dye degradation. The optimized conditions achieved 91.5% removal of 25 mg/L EBBR dye at the reaction conditions: [G-FeNPs] = 0.8 g/L, [H2O2] = 4 mmol/L, pH=3, 60 min contact time, and at room temperature. Four kinetic models were employed to study the reaction kinetic model favorable; first-order, second-order, Elovich, and Behnajady-Modirshahla-Ghanbary (BMG). In general, Elovich and BMG reaction kinetics models are well fitted to all reactions. The thermodynamic functions, such as ΔGº, ΔHº, and ΔSº, were also investigated. The results obtained indicate that the Fenton-like process of EBBR dye was spontaneous and endothermic.